2018
DOI: 10.3390/nu10101404
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenetic Contributions to Dyslipidemia: A Focus on Physiologically Relevant Pathways of Lipid and Lipoprotein Metabolism

Abstract: Cardiovascular disease (CVD) remains the number one cause of death worldwide, and dyslipidemia is a major predictor of CVD mortality. Elevated lipid concentrations are the result of multiple genetic and environmental factors. Over 150 genetic loci have been associated with blood lipid levels. However, not all variants are present in pathways relevant to the pathophysiology of dyslipidemia. The study of these physiologically relevant variants can provide mechanistic understanding of dyslipidemia and identify po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 113 publications
0
16
0
2
Order By: Relevance
“…Dyslipidemia is the combination result of the environmental (diet) factors and genetic factors [ 10 ]. After the human genome project completed, genome wide association studies have revealed many loci that may influence the lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyslipidemia is the combination result of the environmental (diet) factors and genetic factors [ 10 ]. After the human genome project completed, genome wide association studies have revealed many loci that may influence the lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The lipid metabolism could be affected by specific genetic variation [ 10 ], common single-nucleotide polymorphisms (SNPs) modulate the individual response to the diet which could explain how gene-diet interactions affect lipid metabolism [ 11 ]. The effect of any single SNP on the risk of coronary heart disease (CHD) is however, too small, so the definition of genetic risk score (GRS) has arisen based on the combined impact of multiple SNPs leading to CHD [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make the aggressive management of dyslipidemia necessary. There are several risk factors for dyslipidemia, including metabolic capacity, genetic problems, physical inactivity, and dietary habits [ 9 , 10 ], and its progression is a complex process due to dietary nutrition and metabolism being influenced by genetic factors. Modifications to the metabolism of lipid proteins are also involved in dyslipidemia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a literature review [8] and search of the NCBI database (https://www.ncbi.nlm.nih.gov/snp/), 23 SNPs in 15 genes involved in lipid and lipoprotein metabolism were identified that had been previously associated with blood lipid concentrations in humans and were functional (missense) variants, upstream transcription variants, or intronic variants previously associated with phenotypes of interest. The full list of included SNPs, previous associations with dietary fat and blood lipid concentrations, global and sample MAF is presented in Table 1.…”
Section: Genetic Analysis and Snp Selectionmentioning
confidence: 99%
“…Examination of SNPs in the genes relevant to dietary fat and lipoprotein metabolism can potentially provide a mechanistic insight into the pathophysiology of dyslipidemia [6]. The concept that the interactions between diet and physiologically relevant genetic variants affect dyslipidemia phenotypes has been previously reviewed [7,8]. Dietary fat, alcohol, and adherence to a Mediterranean diet have been shown to interact with variants in cholesterol esterase transfer protein (CETP), hepatic lipase (LIPC), and glucokinase regulator protein (GCKR) to associate with blood lipid concentrations in healthy adults [9][10][11].…”
Section: Introductionmentioning
confidence: 99%